Rupture of the Posterior Cruciate Ligament: Preoperative and Postoperative Assessment - Parkar, Anagha P.; Alcalá-Galiano, Andrea (Seminars in Musculoskeletal Radiology, 2016)
Posterior cruciate ligament (PCL) ruptures are not common, but reconstruction is increasing because PCL-deficient knees are prone to develop osteoarthritis. Preoperative MRI may confirm a total or partial disruption of PCL fibers. An overstretched PCL is often mistaken for an intact PCL while the knee is functionally PCL deficient, resulting in false-negative MRI reports. Posterior translation of the medial condyle is a useful indirect sign on imaging. Preoperative stress radiographs are used to quantify the degree of PCL deficiency, and posterior translation determines whether to treat conservatively or with surgery. Early postoperative imaging is performed to evaluate tunnel placement and fixation devices. Late postoperative imaging is performed to assess graft rupture, arthrofibrosis, or tunnel widening. Pre- and postoperative imaging plays an important part in planning and treating functionally PCL-deficient knees and PCL ruptures.
Keywords: PCL rupture; stress radiographs; postoperative imaging; CT; MRI